2017
DOI: 10.1186/s12906-017-1641-3
|View full text |Cite
|
Sign up to set email alerts
|

N-butanol extracts of Morinda citrifolia suppress advanced glycation end products (AGE)-induced inflammatory reactions in endothelial cells through its anti-oxidative properties

Abstract: BackgroundAdvanced glycation end products (AGEs), senescent macroprotein derivatives formed during a normal aging process and acceleratedly under diabetic conditions, play a role in atherosclerotic cardiovascular disease. AGEs cause endothelial cell (EC) damage, an initial trigger for atherosclerosis through the interaction with a receptor for AGEs (RAGE). We have previously shown that n-butanol extracts of Morinda citrifolia (noni), a plant belonging to the family Rubiaceae, block the binding of AGEs to RAGE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
1
19
0
5
Order By: Relevance
“…ROS participates in many intracellular pathological changes. 6,7 In accord with our and other previous studies, ROS triggers programmed cell death through the mitochondrial pathway, death receptor pathway, and endoplasmic reticulum stress-mediated pathway. [8][9][10] Previous studies indicated that AGEs induced endothelial cell apoptosis by exacerbating ROSmediated apoptosis.…”
supporting
confidence: 90%
“…ROS participates in many intracellular pathological changes. 6,7 In accord with our and other previous studies, ROS triggers programmed cell death through the mitochondrial pathway, death receptor pathway, and endoplasmic reticulum stress-mediated pathway. [8][9][10] Previous studies indicated that AGEs induced endothelial cell apoptosis by exacerbating ROSmediated apoptosis.…”
supporting
confidence: 90%
“…Consistent with previous papers (Hirazumi & Furusawa, ; Nayak & Mengi, ; Palu et al, ), these results suggest that Mc‐eWE plays an immunostimulatory role in macrophages in vitro by inducing the mRNA expression of inflammatory mediators that are critical for protecting the body. In previous reports, however, solvent fractions such as ethanol, ethyl acetate, and butanol fractions of noni fruits reduced in vitro inflammatory responses in LPS‐stimulated RAW264.7 cells, H. pylori ‐infected AGS cells, and advanced glycation end product‐exposed human umbilical vein endothelial cells, and in vivo responses in dextran sulfate sodium‐induced colitis showing suppression of NO production and cytokine expression such as TNF‐α and IL‐1β (Coutinho de Sousa et al, ; Ishibashi et al, ; Kim et al, ; Liu et al, ; Nitteranon, Zhang, Darien, & Parkin, ). Although it is not fully elucidated yet, such opposite effects observed under inflammatory conditions could be due to different extraction or preparation methods such as simple squeezing versus sequential extraction, water versus organic solvents, or different origin of fruits such as Hawaii, Costa Rica, or Brazil to affect the composition of active components.…”
Section: Resultsmentioning
confidence: 90%
“…Several in vitro studies have indicated that noni fruit may be helpful in controlling the formation of advanced glycation end products (AGEs) and may subsequently reduce their adverse effects. An extract from noni fruit collected in French Polynesia prevented AGE-induced reactive oxygen species generation in human umbilical vein endothelial cells [ 63 ]. This extract also inhibited the in vitro formation of glucose-human serum albumin, glucose-collagen, and glucose-keratin AGEs as well exhibited AGE-crosslink breaking activity [ 64 ].…”
Section: Control Of Advanced Glycation End Products (Ages) and Glymentioning
confidence: 99%